Effect of Ce addition on microstructure, thermal and mechanical properties of Al-Si alloys - Cengiz, Sezgin; Aboulfadl, Hisham; Thuvander, Mattias (Elsevier, 2023)
In this study, commercial Al-12Si and Al-12Si-xCe (x = 0.5, 1, 2, 4, 8 and 12 wt% Ce) alloys were synthesized and the effect of cerium (Ce) content on the microstructure and on thermal and mechanical properties of the alloys was systematically investigated. The coefficient of thermal expansion decreased from 25.9 x 10-6 K-1 to 23.3 x 10-6 K-1 (50-493 degrees C) with increasing amount of Ce in the alloys. XRD analyses revealed that & alpha;-Al, Si, and CuZn5 were present in all of the alloys. The addition of Ce resulted in the formation of Al9FeSi3, Al0.85CeSi1.15 and AlCeSi2. The chemical composition of the alloy and the existing phases was investigated with energy dispersive spectroscopy in a scanning electron microscope at micrometer scale and with atom probe tomography at nanometer scale in three dimensions. Ce was found to be exist within eutectic Si and Ce-rich intermetallic phases. The addition of 2 wt% Ce into the Al-12Si alloy improved the ultimate tensile strength of the alloy by 25-30%. Further Ce addition (4-12 wt%) resulted in a dramatic drop in the strength of the alloy. The low ductility of the Al-12Si alloy was remarkably improved for the alloys containing Ce up to 2 wt%.
Keywords: Cerium; Aluminum alloy; Al -Si alloy; Atom probe tomography; Fracture strain